Application of the hybrid electrocoagulation-electrooxidation process for the degradation of contaminants in acidified biodiesel wastewater - Guvenc, Senem Yazici; Varank, Gamze; Can-Guven, Emine; Ercan, Hatice; Yaman, Dilan; Saricam, Enes; Turk, Oruc Kaan (ELSEVIER SCIENCE SA, 2022)
In this study, the treatment of biodiesel production wastewater by the hybrid Electrocoagulation (EC) -Electrooxidation (EO) processes was investigated. Before the hybrid process, biodiesel production wastewater was acidified using H2SO4 and HCl at different pH values. The highest pollutant removal efficiency was achieved at pH 6 using HCl. The chemical oxygen demand (COD), total suspended solids (TSS), and oil-grease removal efficiency were 67.2 %, 65.7 %, and 56.9 % after the acidifying of the wastewater. After the applica-tion of the acidification technique, the operating conditions of the EC and EO processes were optimized, then the hybrid EC-EO process was applied. Different electrodes were evaluated and the Al-Al electrode pair was chosen for the EC process while Ti/SnO2 anode was chosen for the EO process. Optimum operational condi-tions for the EC process were 0.25 A and 60 min whereas 0.5 A and 150 min for the EO process while pH was kept as the outlet of the acidification. The COD, TSS, and oil-grease removal efficiency of the hybrid ECopt-EOopt process was 98.9, 98.2, and 99.8 %, respectively. The specific energy consumption of the EC, EO, and hybrid EC-EO processes at optimized conditions were 1.02, 43.4, and 37.4 kWh/kg CODremoved, respec-tively. The hybrid process has a higher removal efficiency than either the EC or EO procedures alone, while it uses less energy than the EO process. The hybrid EC-EO procedure, is an effective treatment method for acid-ified biodiesel wastewater, according to the results of the study.
Keywords: Hybrid Process; Electrocoagulation; Electrooxidation; Energy consumption; Kinetic models; LANDFILL LEACHATE; ELECTROCHEMICAL OXIDATION; SANITARY-LANDFILL; REMOVAL; DESIGN; ACID; OPTIMIZATION; COAGULATION; EFFLUENT; Chemistry; Electrochemistry